A Qualitative Study of Young Men Who Have Sex With Men and Multilevel Factors Related to HIV Risks in Malaysia - Burch, William J.; Hart, Graham J.; Lim, Sin How (Guilford Press, 2018)
Young men who have sex with men (YMSM) are a group at high risk for HIV infection, yet no research has been conducted to understand this population in Malaysia. Semistructured interviews from a combination of YMSM aged 18–25 (n = 20) and local service providers of sexual health services (n = 4) were conducted from May to June 2015. Thematic analysis was used to identify common themes in participant responses from transcripts. Participants reported societal and internalized homophobia, an absence of sex education and difficulty accessing confidential HIV testing. This study provides insights into how homophobia in Malaysian society influences individual risk behavior for HIV in Malaysian YMSM, and makes practical suggestions for more effective HIV prevention in this population.